Developing Green Entrepreneurs Among Generation Z: The Role of Education, University Support, and Self-Efficacy in Promoting Student Innovation - Maria Carmelita Bulu; Resti Logo; Fernando Saragih; Retno Hernawati (Airlangga Journal of Innovation Management, 2026)
Students in East Nusa Tenggara Province demonstrate low interest in green entrepreneurship due to a limited understanding of environmentally friendly business practices. This study aims to analyze the influence of entrepreneurship education and university support on students’ interest in green entrepreneurship, with entrepreneurial self-efficacy serving as a mediating variable. The research employed a quantitative approach using a survey method involving 150 students selected through incidental sampling. Data were collected using a questionnaire comprising 55 validated and reliable items and analyzed through path analysis after confirming all classical assumptions were met. The findings reveal that entrepreneurship education and university support significantly influence students’ green entrepreneurial intentions directly, while the mediating effect of entrepreneurial self-efficacy is not significant. This indicates that strengthening educational content and institutional support play a crucial role in enhancing students’ interest in green entrepreneurship, although self-efficacy does not act as a significant mediator. The study recommends that universities integrate environmental themes into entrepreneurship courses, provide mentoring and funding for sustainable business projects, and facilitate practical experiences to promote students’ engagement in green entrepreneurship.